Convergent and Discriminant Validity of the Test of Passive Aggression in a Psychotherapy Outpatient Sample - Schanz, Christian Günter; Equit, Monika; Schäfer, Sarah K.; Michael, Tanja (Frontiers in Psychology, 2021)
Background: While most clinical aggression questionnaires focus on the assessment of active aggression the recently developed Test of Passive Aggression (TPA) assesses both self-directed (TPA-SD) and other-directed passive aggression (TPA-OD). Reliability and factorial validity of the TPA have been demonstrated in a clinical sample, while previous evaluations of convergent and discriminant validity were limited to student samples. The current study aimed at addressing this gap by demonstrating convergent and discriminant validity of the TPA in an outpatient sample. Methods: Eighty-two patients admitted to an outpatient psychotherapy unit at Saarland University, Germany, participated in the preregistered study with an assessment of self-reported passive aggression, impulsivity, anger expression, self- compassion, self-esteem and auto-aggressive mindset. Analyses used regression models with robust maximum likelihood estimations. Results: Self-directed passive aggression showed a significant association with self-compassion, auto-aggressive mindset, self-esteem and internal anger expression supporting the convergent validity of TPA-SD. Results on discriminant validity of TPA-SD were heterogenous at the first sight, revealing small associations of self-directed passive aggression with anger control but medium associations with impulsivity. However, exploratory analysis showed that the medium association with impulsivity was driven by the non-behavioral impulsivity dimension ‘inattention’ and that both behavioral impulsivity dimensions (‘motor-impulsivity’ and ‘unplanned behavior’) demonstrated only weak associations with TPA-SD. Validity of TPA-OD was not supported by the current study. Conclusion: Our findings provide evidence for validity of the TPA-SD to outpatient samples. Future studies will need to analyse construct validity based on a nomological network using larger and more diverse samples.